Strategi Belajar Mengajar - Nurhayani Nurhayani; Fadillah Ramadhani Asiri; Rianti Simarmata; Yisawinur Barella (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The Project Based Learning (PBL) method has become a major focus in the world of education because of its potential to increase student engagement and understanding of concepts in social studies subjects. This research aims to explore the implementation of PBL in social studies learning. Using essential questions as a basis, project activities are designed to facilitate an interactive and comprehensive teaching and learning process. In addition, an activity schedule is created to provide guidance in project planning and implementation. Assessments are carried out to evaluate student learning outcomes, while experience reflection aims to improve future learning experiences.